ESTUDO ANALÍTICO DOS POÇOS DA BACIA SEDIMENTAR DE ALAGOAS (1) - CAVALCANTE, A. T.; Wanderley, P. R. M.; Neto, J. V. F.; Barroso, C. M. R.; Ramalho, W. M.; Lima, R. C. (Águas Subterrâneas, 1992)
INDISPONÍVEL